Ler of pathogenic Escherichia coli forms toroidal protein–DNA complexes - Mellies, Jay L. (Microbiology Society, 2011)
Enteropathogenic and enterohaemorrhagic Escherichia coli are related pathotypes of bacteria that cause acute watery diarrhoea and haemorrhagic colitis, respectively, and enterohaemorrhagic E. coli can lead to a serious complication known as haemolytic uraemic syndrome. In both bacteria the global regulatory protein Ler controls virulence. The ler gene is found within the locus of enterocyte effacement, or LEE, encoding a type III secretion system necessary for injecting effector proteins into intestinal epithelial cells and causing net secretory diarrhoea. The nucleoid-associated protein H-NS silences, whereas Ler serves as an anti-silencer of, multiple LEE operons. Although Ler has a higher affinity for DNA than does H-NS, the precise molecular mechanism by which Ler increases LEE transcription remains to be determined. In this report we investigate the oligomerization activity of Ler. In solution, Ler forms dimers and soluble aggregates of up to 5000 kDa molecular mass, and appears to oligomerize more readily than the related protein H-NS. An insertional mutation into the Ler linker region diminished oligomerization activity. Despite being proteins of similar mass and having homologous DNA-binding domains, Ler and H-NS complexed to DNA migrated to distinct locations, as determined by an electrophoretic mobility shift assay, implying that the related proteins form different 3D shapes in the presence of DNA. Lastly, we present electron microscopy images of toroidal Ler–DNA structures that are predicted to be involved in stimulating gene expression.